Investigation of senses of sexism and religiosity in terms of sports variable - Duygu Yaralı; Erkan Bıngol; Gulsum Bastug (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to investigate senses of sexism and religiosity in terms of sports variable.  Totally 192 university students including 121 males and 71 females with an average age of 21.72 ± 1.90 voluntarily participated in the research. “Ambivalent Sexism Inventory” was used in order to measure the attitudes of students participated in the research towards sexism whereas “Religiosity Scale” was used to determine their sense of religiosity. For the assessment of the results, frequency, t-test and correlation statistical processes were carried out.As a result; a significant difference was found between individuals doing and not doing exercises in terms of their sexism and religiosity levels. A significant difference was also found between hostile sexism, benevolent sexism and benevolent patriarchy attitudes of individuals doing and not doing exercises. It was determined that average of hostile sexism, benevolent sexism and benevolent patriarchy attitudes of individuals doing exercises was higher than that of individuals not doing exercises. A significant difference was determined between hostile sexism, benevolent sexism and heterosexual intimacy properties in terms of gender variable. It was observed that hostile sexism property of females was lower than that of male participants. On the other hand, benevolent sexism property of females was higher than that of male participants. A significant difference was not found between doing exercises variable, gender variable as well as religiosity variable, however, a positive relationship was found between religiosity and benevolent sexism, heterosexual intimacy, benevolent, supplementary attitude towards genders. As the level of religiosity increases, the average of benevolent sexism, heterosexual intimacy, benevolent patriarchy, supplementary attitude towards genders also increases.